Satisfaction with service coverage and drug list may influence patients' acceptance of general practitioner contract service: a cross-sectional study in Guangdong, China - Aiyun Chen; Shanshan Feng; Wenxi Tang; Liang Zhang (BMC, 2019)
Abstract Background General practitioner (GP) system is proved to be effective in over 50 countries worldwide. Guangdong province, as a reform pilot in China, initiated its patient-GP contract service reform in 2014. This study is designed to assess the patients' acceptance of General Practitioners Contract (GPC) reform and explore its influencing factors. Methods This survey interviewed 1010 participants from 16 primary health centers (PHCs) chosen from 4 pilot cities in Guangdong during July and December in 2015. Data were collected through face-to-face interviews. The questionnaire was developed to discover the acceptance of GPC and covered three parts: respondents' socio-demographic characteristics, health service utilization, and the patients' assessment of primary health care centers. A binary logistic regression model was used to measure the influencing factors of respondents' acceptance of GPC policy. Results A total of 611(60.5%) participants accepted GPC policy. Compared to patients visited PHCs over 7 times in the previous year, those visited PHCs fewer times reported lower acceptance of GPC policy (OR:0.68, 95% CI:0.49-0.96 for visits ≤3 times and OR:0.57, 95% CI:0.38-0.84 for visits = 4-6 times). Patients' satisfaction with medical service coverage was positively associated with patients' acceptance of GPC (OR: 1.72, 95% CI:1.01-3.98 for the satisfied versus the dissatisfied; OR: 1.38, 95% CI:0.92-3.30 for neutral versus the dissatisfied), and the satisfaction with drug list also positively influenced patients' acceptance of GPC policy (OR: 1.44, 95% CI:1.26-2.73 for the satisfied versus the dissatisfied; OR:1.61, 95% CI:1.36-2.99 for neutral versus the dissatisfied). Meanwhile, age and education had positive impacts on the acceptance of the GPC policy. Conclusion This study finds out that patients' satisfaction with medical service coverage and drug list are the influencing factors for the acceptance of GPC policy. Therefore, improvement of medical service accessibility such as better follow-up of patients with chronic diseases and enhanced referral service, as well as the expansion of drug list, will improve patients' acceptance of GPC policy. It also finds that patients using more primary health service are inclined to accept GPC policy, so more attractive and high-quality service should be provided in PHCs.